Effectiveness of Renin-Angiotensin-Aldosterone System Blockade on Residual Kidney Function and Peritoneal Membrane Function in Peritoneal Dialysis Patients: A Network Meta-Analysis - Sirayut Phatthanasobhon (2020)
© 2019, The Author(s). We performed a network meta-analysis of randomised controlled trials (RCTs) and non-randomised studies in adult peritoneal dialysis patients to evaluate the effects of specific renin-angiotensin aldosterone systems (RAAS) blockade classes on residual kidney function and peritoneal membrane function. Key outcome parameters included the following: residual glomerular filtration rate (rGFR), urine volume, anuria, dialysate-to-plasma creatinine ratio (D/P Cr), and acceptability of treatment. Indirect treatment effects were compared using random-effects model. Pooled standardised mean differences (SMDs) and odd ratios (ORs) were estimated with 95% confidence intervals (CIs). We identified 10 RCTs (n = 484) and 10 non-randomised studies (n = 3,305). Regarding changes in rGFR, RAAS blockade with angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin II receptor blockers (ARBs) were more efficacious than active control (SMD 0.55 [0.06–1.04] and 0.62 [0.19–1.04], respectively) with the protective effect on rGFR observed only after usage ≥12 months, and no differences among ACEIs and ARBs. Compared with active control, only ACEIs showed a significantly decreased risk of anuria (OR 0.62 [0.41–0.95]). No difference among treatments for urine volume and acceptability of treatment were observed, whereas evidence for D/P Cr is inconclusive. The small number of randomised studies and differences in outcome definitions used may limit the quality of the evidence.